Communicating Down syndrome risk according to maternal age: "1‐in‐X" effect on perceived risk. (9th June 2015) - Pighin, Stefania; Savadori, Lucia; Barilli, Elisa; Galbiati, Silvia; Smid, Maddalene; Ferrari, Maurizio; Cremonesi, Laura
Abstract Objective The appropriateness of the 1‐in‐X numerical format to convey quantitative medical probabilities is currently under discussion because of its distortive effect on subjective probability assessment. Previous research, however, always asked participants to imagine a hypothetical scenario. The aim of the present research is to support the existence of the 1‐in‐X effect in a real setting: when pregnant women have to evaluate their personal risk of Down syndrome according to their maternal age. Method During the first prenatal visit, pregnant women were asked to evaluate their own risk of having a child with Down syndrome according to their age, when such risk was presented either in the 1‐in‐X or in the N‐in‐NX format. Then, they were asked to assess their risk of having a child with Down syndrome. Results Results showed a systematic higher risk assessment when pregnant women were presented with the 1‐in‐X format (mean = 3.57, standard deviation = 1.4) than with the N‐in‐NX format (mean = 3.03, standard deviation = 1.4), P = 0.007. Whereas the effect was shown to be not moderated by a differential comprehension of the two numerical formats, women with a low educational level and those who were at their first pregnancy were shown to be significantly more vulnerable. Conclusion The present findings corroborate the existence of the 1‐in‐X effect in a real‐world setting, showing that, in pregnant women, the 1‐in‐X format actually elicits a higher perceived risk of Down syndrome, compared with the N‐in‐NX format. © 2015 John Wiley & Sons, Ltd.